All-optical design for inherently energy-conserving reversible gates and circuits - Eyal Cohen (Nature Portfolio, 2016)
Reversible gates, like Fredkin gates, may be useful for energy conservation efforts. Cohen et al. present a formalism that may be used to produce any reversible logic. This method is implemented over an optical design of the Fredkin gate which utilizes only optical elements that inherently conserve energy.